Mixed Methods Research in Poverty and Vulnerability
XIII, 281 p. 8 illus.
Keywords: The added value of mixed methods research in poverty and vulnerability is now widely established. Nevertheless, gaps and challenges remain. This volume shares experiences from research in developed and developing country contexts on how mixed methods approaches can make research more credible, usable and responsive to complexity. .